Characterization of lymphocytic choriomeningitis virus-binding protein(s): a candidate cellular receptor for the virus. - Borrow, P; Oldstone, M (1992)
The attachment of lymphocytic choriomeningitis virus (LCMV) to murine and primate cell lines was quantitated by a fluorescence-activated cell sorter assay in which binding of biotinylated virus was detected with streptavidin-fluorescein isothiocyanate. Cell lines that were readily infected by LCMV (e.g., MC57, Rin, BHK, Vero, and HeLa) bound virus in a dose-dependent manner, whereas no significant binding was observed to lymphocytic cell lines (e.g., RMA and WIL 2) that were not readily infected. Binding was specific and competitively blocked by nonbiotinylated LCMV. It was also blocked by LCMV-specific antiserum and a neutralizing monoclonal antibody to the virus glycoprotein GP-1 but not by antibodies specific for GP-2, indicating that attachment was likely mediated by GP-1. Treatment of cells with any of several proteases abolished LCMV binding, whereas phospholipases including phosphatidylinositol-specific phospholipase C had no effect, indicating that one or more membrane proteins were involved in virus attachment. These proteins were characterized with a virus overlay protein blot assay. Virus bound to protein(s) with a molecular mass of 120 to 140 kDa in membranes from cell lines permissive for LCMV but not from nonpermissive cell lines. Binding was specific, since unlabeled LCMV, but not the unrelated enveloped virus herpes simplex virus type 1, competed with 125I-labeled LCMV for binding to the 120- to 140-kDa band. The proteinaceous nature of the LCMV-binding substance was confirmed by the lack of virus binding to proteinase K-treated membrane components. By contrast, glycosidase treatment of membranes did not abolish virus binding. However, in membranes treated with endoglycosidase F/N-glycosidase F, and/or neuraminidase and in membranes from cells grown in tunicamycin, the molecular mass of the LCMV-binding entity was reduced. Hence, LCMV attachment to rodent fibroblastic cell lines is mediated by a glycoprotein(s) with a molecular mass of 120 to 140 kDa, with complex N-linked sugars that are not involved in virus binding.